One-year follow-up after the time management group intervention Let's Get Organized. (19th May 2022) - Wingren, Maria; Lidström-Holmqvist, Kajsa; Roshanai, Afsaneh Hayat; Arvidsson, Patrik; Janeslätt, Gunnel; White, Suzanne; Holmefur, Marie
Abstract: Background: Time management skills are essential to maintain occupations in everyday life. People with neurodevelopmental or mental disorders often experience persistent difficulties with managing time and organizing daily life, consequently, there is a need to establish interventions with sustainable results. Aim: The aim was to perform a one-year post-intervention follow-up after the intervention Let's Get Organized (LGO-S) for people with neurodevelopmental or mental disorders. Methods: The study is a one-year follow-up of a single group pre-test–post-test design. Thirty-eight persons with difficulties in time management due to neurodevelopmental or mental disorders participated. Instruments to collect data were Assessment of Time Management Skills; Weekly Calendar Planning Activity and the Satisfaction with Daily Occupations instrument. Wilcoxons's signed-rank test was used to compare data over time. Results: There were no significant differences in the participants' outcomes between post-intervention and one-year follow-up in time management skills and regulation of emotions, satisfaction with daily occupations, and global satisfaction. A significant improvement could be seen in the subscale organization and planning at the one-year follow-up compared to post-intervention. Conclusions: Improvements in time management skills, organization, and planning, regulation of emotions, and satisfaction with daily occupations after the LGO-S can be maintained in the long term.